2022
DOI: 10.3390/ani12202835
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of the Human–Animal Bond: Empathy, Attachment and Anthropomorphism in Human–Animal Relationships and Animal Hoarding

Abstract: The human–animal relationship is ancient, complex and multifaceted. It may have either positive effects on humans and animals or poor or even negative and detrimental effects on animals or both humans and animals. A large body of literature has investigated the beneficial effects of this relationship in which both human and animals appear to gain physical and psychological benefits from living together in a reciprocated interaction. However, analyzing the literature with a different perspective it clearly emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 286 publications
2
14
0
Order By: Relevance
“…As far as the individual is concerned, several causes are listed in the literature such as: gender -it is proven that women are more empathetic than men [56]; culture -authors such as Losada-Espinosa et al [33] state that conditions as ethnicity, educational backgrounds, health condition, culture, generational differences and occupational roles condition the quality of attitudes to animals on farms; technical training -"capacity" is the junction of technical skills and knowledge that Hemsworth, adapting from Blumberg and Pringle (1982), considers one of the types that contribute to a good work performance of farm [57]; empathy -together with "attachment" and "anthromorphism" is considered by some authors to be one of the determining factors in human-animal relationships [58]; pleasure in doing their jobthe working conditions and motivation of the workers will affect their performance with the animals [57]; love for animals [59] -a study published in 2018 linked the type of love existing between partners with the type of attitudes towards their pets. It was found that erotic love is linked to positive attitudes, while a playful type of love is related to negative attitudes; and having had contact with animals as a child -E. Paul found out in a study, from 2000, that past and present pet owning was associated with higher levels of animal-oriented empathy but, very interestingly, not humanoriented empathy [60].…”
Section: Influencing Factorsmentioning
confidence: 99%
“…As far as the individual is concerned, several causes are listed in the literature such as: gender -it is proven that women are more empathetic than men [56]; culture -authors such as Losada-Espinosa et al [33] state that conditions as ethnicity, educational backgrounds, health condition, culture, generational differences and occupational roles condition the quality of attitudes to animals on farms; technical training -"capacity" is the junction of technical skills and knowledge that Hemsworth, adapting from Blumberg and Pringle (1982), considers one of the types that contribute to a good work performance of farm [57]; empathy -together with "attachment" and "anthromorphism" is considered by some authors to be one of the determining factors in human-animal relationships [58]; pleasure in doing their jobthe working conditions and motivation of the workers will affect their performance with the animals [57]; love for animals [59] -a study published in 2018 linked the type of love existing between partners with the type of attitudes towards their pets. It was found that erotic love is linked to positive attitudes, while a playful type of love is related to negative attitudes; and having had contact with animals as a child -E. Paul found out in a study, from 2000, that past and present pet owning was associated with higher levels of animal-oriented empathy but, very interestingly, not humanoriented empathy [60].…”
Section: Influencing Factorsmentioning
confidence: 99%
“…Emotion is represented by the emotional bond and love for nature, such as talking and reflecting on one’s feelings about it, which can contribute to its conservation. Lastly, Compassion seeks to extend the self to include nature, leading to a moral and ethical concern for nature, for example: making ethical choices of products, caring for plants and animal welfare ( Lumber et al, 2017 ; Choque, 2021 ; Prato-Previde et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The intricate relationship between humans, attachment and animals has been the subject of extensive research, delving into various aspects including deep interactions, empathy development, and animal welfare [ 1 , 2 , 3 , 4 ]. The term pets has evolved into companion animals to reflect their significant role and emotional connections with humans [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Companion animals provide social support, as evidenced by animal-assisted activities and pet-friendly workplaces, which enhance employee satisfaction and productivity [ 2 , 30 ]. Especially during the COVID-19 pandemic, companion animals served as a form of social support, preserving the identity of their owners in challenging situations [ 2 , 4 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation